The role of nocturnal and diurnal pollinators in the commercial production of Dragon Fruit crops in Costa Rica - Villegas-Murillo, Jordán; Fernández Otárola, Mauricio (Revista de Biología Tropical, 2025)
Introduction: Dragon fruit (or pitahaya) cultivation is of growing interest in Central America. Several species of the genus Selenicereus (Cactaceae) are cultivated around the world, with S. costaricensis being the only species native to this region. The pollination syndrome of the species partially matches chiropterophily and phalaenophily, but floral visitors and their effect on commercial fruit production is not well known. Objective: To analyze the reproductive system, the floral visitors and their effect on fruit size in plantations of S. costaricensis in Costa Rica. Methods: We recorded the anthesis period, stigmatic receptivity, anther dehiscence and nectar production. We conducted pollination experiments (manual self- and cross-pollination) and evaluated the effect of nocturnal and diurnal natural pollination on fruit production and traits related to fruit size and weight. Flower visitors were filmed, identified, quantified, and their behavior was documented. Results: Plants were self-compatible. All pollination treatments produced viable fruits, but there were differences in fruit weight and size. Natural pollination, nocturnal and diurnal combined, produced the biggest fruits, while self-pollination the smallest. The fruits generated by either nocturnal or diurnal pollinators were of good commercial size. Hawk moths and bees were the main pollinators; no visits by bats were detected. The flowers produced no measurable nectar volume. Mass visitation by bees in periods of 15–20 minutes at dawn was sufficient to produce large fruits. Conclusions: Diurnal and nocturnal pollinators are equally effective producing highly profitable fruits. The management of Apis mellifera and native solitary bee species is recommended to increase production efficiency in these plantations. Manduca rustica hawk moths seem the natural pollinators of S. costaricensis, and bats played no role in the production of fruits.